Sensitivities : Contemporary Art from Central Europe. - Hegyi, Lóránd; Valencak, Agnes; European Academy for the Arts, London (Wien : Museum moderner Kunst Stiftung Ludwig, 1998)
Balka, Miroslav ; Dimitrijevic, Braco ; Dopitová, Milena ; El-Hassan, Róza ; Feher, Laszlo ; Fila, Rudolf ; Hencze, Tamas ; Jovanovics, Gyorgy ; Kolibal, Stanislav ; Kovanda, Jiri ; Malich, Karel ; Mosbacher, Alois ; Mulasics, Laszlo ; Petercol, Goran ; Potrc, Marjetica ; Reiterer, Werner ; Schlegel, Eva ; Weinberger, Lois ; West, Franz
biografie
Sensitivities : Contemporary Art from Central Europe, European Academy for the Arts, London, 24 June - 30 August 1998
Engels
kunstcatalogus
Keywords: Midden-Europa